Analisis Struktural Puisi “Tiada” Karya Joko Pinurbo - Silva Caesarani Destiana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Poetry is one type of literary work in which there are a series of words that contain meaning. Therefore, to understand more deeply about the poem requires an in-depth study. The purpose of this study is to describe the structure of the poem where there are physical elements and mental elements in the poem "Tiada" by Joko Pinurbo. The method in this study is qualitative descriptive which is studied using a structural analysis approach. The results of the structural analysis of this poem contain the physical structure analyzed including diction, imaging, majas, and typography. While the mental structure analyzed includes themes, feelings, tones and gymnasals, and messages. This research is useful for readers to better understand the content of poetry and develop insight or knowledge of literary works in the form of poetry, especially in analyzing its structure.